Tilapia Fish and Vegetable Cultivation Using the Aquaponic System as an Economic Driver for the Mee Tanjong Usi Village Community in Pidie Regency - Dewi, Ervina; Agustina, Rahmi; Murdani, Khairul; Fadhil, Muhammad; Azhari (Unram Journal of Community Service, 2025)
Gampong Mee Tanjong Usi is located in Mutiara Timur District, Pidie Regency, Aceh Province, and has residents whose main livelihood is as farmers. The dense population makes agricultural land scarce. Aquaponic cultivation system is an innovation offered as a solution. The Aquaponics system combines a hydroponic system and an aquaculture system. This PKM activity aims to increase the knowledge and skills of the “Mee Meuhase” group from Gampong Mee Tajong Usi in managing aquaponic systems, producing local food products and increasing income. The implementation method begins with observation and outreach, training and assistance in creating an Aquaponics system, application of technology as well as monitoring and evaluation of program sustainability. The fish seeds cultivated are tilapia (Oreochromis niloticus) and the vegetables grown are spinach (Amaranthus sp) and pokcoy (Brassica rapa L.). As a result of the implementation of the activity, the activity went well with high enthusiasm from the participants. Education and training that assembles, manages aquaponic systems, produces environmentally friendly products, increases environmental awareness and helps increase income.